A geographic carbon emission estimating framework on the city scale. (20th January 2020) - Wang, Gengzhe; Han, Qi; de Vries, Bauke
Abstract: To facilitate sustainable carbon management on the city scale, estimating carbon emissions is necessary for determining carbon reduction targets. Although many studies have focused on mitigating GHG emission through industrial sector optimization and energy efficiency improvement, limited research was conducted to reduce carbon emission based on spatial planning. This paper proposes a comprehensive carbon emission estimation framework based on GIS technology with open data. It presents the spatial distribution of carbon emission on the city scale. The sectors of carbon emissions are mainly attributed to buildings, transportation, vegetation, and residence. Statistic data was applied to estimate the carbon emission in buildings and residence sectors. Transport carbon emission was calculated through a bottom-up method with the support of the logistic regression model and spatial microsimulation. Carbon sequestration of vegetation was estimated by remote sensing technology. Eindhoven was employed as a case study to verify the feasibility of the framework. The results clearly illustrate the carbon balance in association with land use patterns. The new framework can be used to analyze the impact of urban spatial planning on carbon emission. The estimation results can also apply to urban form components (land use, buildings types, and road network) optimization and environmental assessment.